2020
DOI: 10.1016/j.heliyon.2020.e05068
|View full text |Cite
|
Sign up to set email alerts
|

Mode of delivery, order of birth, parental age gap and autism spectrum disorder among Malaysian children: A case-control study

Abstract: Rising prevalence of autism spectrum disorders (ASD) in the last decades has led research to focus on the diagnosis and identification of factors associated with ASD. This paper sought for possible factors that put children at risk for ASD. In this study, we investigated the association between ASD and parental ages, parental age gaps, birth order and birth delivery method in Malaysian population. In this school-based case control study, 465 children with ASD 464 controls participated. Questionnaires were dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…After adjustment for potential confounding factors, the risk of ASD was 38% higher in children born by CS than in those born by vaginal delivery in this study. In the literature, there are conflicting reports regarding the association between CS and ASD [ 7 , 10 , 11 , 17 ]. Previous studies and a meta-analysis indicated that CS increased the risk of ASD [ 7 , 11 , 17 ], which is line with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After adjustment for potential confounding factors, the risk of ASD was 38% higher in children born by CS than in those born by vaginal delivery in this study. In the literature, there are conflicting reports regarding the association between CS and ASD [ 7 , 10 , 11 , 17 ]. Previous studies and a meta-analysis indicated that CS increased the risk of ASD [ 7 , 11 , 17 ], which is line with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are conflicting reports regarding the association between CS and ASD [ 7 , 10 , 11 , 17 ]. Previous studies and a meta-analysis indicated that CS increased the risk of ASD [ 7 , 11 , 17 ], which is line with the findings of the present study. However, the large cohort study by Zhang et al (2021) in Sweden showed no association between CS and ASD [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased risk in the firstborn child may be related to a higher exposure rate to pregnancy and delivery complications such as infections, stress, and inflammation. In contrast, the lower risk of the later-born children may be related to the social support and help provided by the first-born child to the later-born children[ 42 ]. On the other hand, Alvares et al [ 43 ] showed that intelligence scores and adaptive functioning decrease with increasing birth order.…”
Section: Discussionmentioning
confidence: 99%
“…That means the symptoms/disorders occur during the child's growth and development [5], [6]. Parents should be extra focused on accompanying the development of children with ASD [7], [8]. Caring for children with ASD requires energy, time, and a strong enough financial foundation so that children can grow optimally like other normal children [9], [10].…”
Section: Introductionmentioning
confidence: 99%